2014
DOI: 10.1172/jci74337
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine therapy reverses NK cell anergy in MHC-deficient tumors

Abstract: fit of the cytokine treatment in mice with RMA-S tumors was completely abrogated if the mice were NK-depleted, demonstrating that the effect of the cytokines depended on NK cells ( Figure 1C).The efficacy of cytokine treatments in mice bearing RMA-S tumors did not apply to mice bearing RMA tumors, which are similar to RMA-S cells except that they express high amounts of MHC class I and are therefore resistant to NK cells ( Figure 1B, bottom panel). The survival time in mice with RMA tumors did not change when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
175
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(188 citation statements)
references
References 52 publications
12
175
0
1
Order By: Relevance
“…Especially during the early phase of stem cell or NK cell infusion therapy in which retuning and antileukemic effects occur in parallel, small differences in conditioning regimen, T-cell depletion, or immunosuppression may influence the activation threshold of educated donor NK cells. It would thus be important to prevent adaptation of NK cells to reduced inhibitory input, or to combine the therapy with another NK cell-activating regimen, such as cytokines or ADCC-inducing antibodies (8,9,48).…”
Section: Discussionmentioning
confidence: 99%
“…Especially during the early phase of stem cell or NK cell infusion therapy in which retuning and antileukemic effects occur in parallel, small differences in conditioning regimen, T-cell depletion, or immunosuppression may influence the activation threshold of educated donor NK cells. It would thus be important to prevent adaptation of NK cells to reduced inhibitory input, or to combine the therapy with another NK cell-activating regimen, such as cytokines or ADCC-inducing antibodies (8,9,48).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the concepts of cytokine-induced NK memory cells, a Phase I clinical trial using IL-12, IL-15 and IL-18-pre-activated NK cells for treatment of patients with AML recently opened at Washington University School of Medicine, St Louis, Missouri, USA (NCT01898793). The intratumoural application of the cytokines IL-12 and IL-18 was also shown to revert dysfunction of NK cells in the tumour bed of MHC class I-deficient tumour cells 76 . Whether NK cells with a sustained ability for long-term effector function were generated in these studies has not been evaluated.…”
Section: Exploiting Nk Cell Memory For Antiviral Therapymentioning
confidence: 95%
“…These pre-activated NK cells had better effector functions in vitro, as well as enhanced proliferation, tumour infiltration and tumour control in vivo when tested in mouse models of lymphoma and melanoma 134,135 . Furthermore, recent work by Ardolino et al 136,137 showed that treatment with these cytokines in vivo reversed the tumour-induced anergic state of NK Several challenges must be overcome to optimize the use of NK cells in cancer therapy, including blocking the inhibitory receptors that dampen NK cell activation (FIG. 3a), eliminating T Reg cells that suppress their function, enabling NK cells to traffic into solid tumours, neutrali zing immunosuppressive cytokines such as TGFβ secreted by the tumour (FIG.…”
Section: Using Nk Cells For Cancer Therapymentioning
confidence: 99%